2014
DOI: 10.6000/1927-3037.2014.03.01.1
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Specific Blood Serum Factors as Basis of Tumor Dormancy

Abstract: In the present review, we focus on the importance of blood serum factors for tumor growth in vivo. Data from mice experiments indicate the existence of serum factors, which decrease the dormancy of Ehrlich carcinoma cells from 85 to 20%. The impaired production of these factors increases the life span of tumor-bearing animals from 14 days to 120 days. Blocking the production of tumor-specific factors causes the complete regression of already developed Ehrlich carcinoma. These serum factors do not affect the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…A previous study by our group demonstrated changes in the glycosylation of serum proteins in tumor-bearing mice (1). However, it was not possible to establish a link between the various N-linked oligosaccharide residues and the tumors of animals or cancer patients (1)(2)(3). Another previous study by our group showed that the serpin α-anti-trypsin from blood serum inhibits or blocks the growth of tumors (4).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study by our group demonstrated changes in the glycosylation of serum proteins in tumor-bearing mice (1). However, it was not possible to establish a link between the various N-linked oligosaccharide residues and the tumors of animals or cancer patients (1)(2)(3). Another previous study by our group showed that the serpin α-anti-trypsin from blood serum inhibits or blocks the growth of tumors (4).…”
Section: Introductionmentioning
confidence: 99%
“…The question that arises from these studies is how proteins in the blood serum of tumor-bearing mice as well as in the blood serum of tumor-free mice acquire tumor-associated biological activity. It is known that the blood serum of tumor-bearing animals contains a certain factor which specifically accelerates tumor growth (2,5). However, all attempts to identify this factor as a novel protein in the blood serum of tumor-bearing animals were unsuccessful (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation